Factors for slowing inflation in economy - T. I. Gordiyevich; P. V. Ruzanov (Омский научный вестник: Серия "Общество. История. Современность")
The article continues the multi-factor analysis of inflation processes, which was started in the article «evolution of inflation factors in the conditions of economic sanctions». The article focuses on the analysis of the prevailing factors in 2017. Inflation in 2017 had an unprecedented low growth rate. The main reasons for the slowdown in inflation are the decline in consumer and investment demand. The purpose of the article is to understand the mechanism of influence of various factors on inflation in 2017. The decline in inflation is explained by the tightening of monetary policy. Structural and technological changes that lead to a significant reduction in the cost of new goods and services are also the basis of price reduction. The rapid decline in inflation is due to the fall in real incomes and the effective demand of the population